PROGRAM PARENTING DALAM MENINGGATKAN PEMAHAMAN MASYARAKAT TERHADAP TUMBUH KEMBANG ANAK USIA DINIi - Indrawati Indrawati (Kreasi: Jurnal Pengabdian Masyarakat, 2021)
Parenting is an achievement that must be developed to deepen the knowledge of parents in guiding and nurturing children in preparing a responsible society and good personality in the future as the golden generation. The purpose of this parenting activity is to assist in the development and growth of children, as well as parenting patterns for early childhood, this activity is carried out at the Bunda Salmi PAUD in Sungai Gelam Village. Community service activities use methods in the form of seminars and questions and answers regarding child development problems. The result of this activity is the implementation of parenting for parents of early childhood in good parenting following the growth and development of children.